1991
DOI: 10.1111/j.1365-2427.1991.tb01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Major ion chemistry of the lower Boro River, Okavango Delta, Botswana

Abstract: 1. The composition of surface waters of the Boro River, Okavango Delta, Botswana, was determined on five occasions during [1989][1990]. The waters could be characterized as calcium-sodiumbicarbonate, with moderate alkalinity, and moderate to high amounts of silica. Mean values of the major ions, in mgl"', were: 4.8, 1.3, Na^ 3.9, K^ 2.7, HCOJ 27, CP 1.0 and SiO^ 38; pH c. 7.2. The relative ionic composition of the waters changed gradually from the inlet in Seronga to the outlet at Boro/Thamalakane junction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Some of these cations, for example Ca, are essential for the growth and development of prokaryotes, fungi, and plants, and these organisms may sequester them in biomass. The order of solutes in concentration was Ca > Na > K > Mg, consistent with the findings of Sawula and Martins (1991) and Masamba and Muzila (2005). This was, however, contradictory to results of Mackay et al, (2011) who found a greater concentration of potassium than sodium.…”
Section: System-scale Longitudinal Gradientsupporting
confidence: 79%
See 3 more Smart Citations
“…Some of these cations, for example Ca, are essential for the growth and development of prokaryotes, fungi, and plants, and these organisms may sequester them in biomass. The order of solutes in concentration was Ca > Na > K > Mg, consistent with the findings of Sawula and Martins (1991) and Masamba and Muzila (2005). This was, however, contradictory to results of Mackay et al, (2011) who found a greater concentration of potassium than sodium.…”
Section: System-scale Longitudinal Gradientsupporting
confidence: 79%
“…This implies that there must be some differentiation in the processes affecting individual ions. The concentrations of major cations (Ca, K, Mg and Na) increased generally throughout the Delta for surface waters, similar to the trends reported by Sawula and Martins (1991) and Mackay et al (2011). This correlates well with a general increase in conductivity along the Delta distributaries.…”
Section: System-scale Longitudinal Gradientsupporting
confidence: 75%
See 2 more Smart Citations
“…However, while the hydrology of the Delta has been comprehensively studied (see Milzow et al 2009 for a review), there have been considerably fewer investigations into how the flood pulse in the Delta impacts nutrients (Mubyana et al 2003;Lindholm et al 2007) and inorganic chemistry (Sawula and Martins 1991). Previous studies focussed only on very short time periods (Ashton et al 2003), or were restricted to the Jao / Boro river system (Sawula and Martins 1991;Cronberg et al 1996a,b). Here we report on a large, comprehensive, surface water chemistry dataset that covers four important regions in the Delta, sampled over a complete flood cycle.…”
Section: Introductionmentioning
confidence: 97%